Implementasi Sistem Peramalan Persediaan Barang Menggunakan Metode Moving Average - Wulandari Wulandari (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
PT. XYZ is a company engaged in the sale of drugs and vitamins for livestock, each period the number of requests for goods always changes. Problems faced by PT. XYZ, which is expired goods because in a certain period the amount of stock is piling up due to the small amount of demand that causes the company to lose. The purpose of this study is to forecast the inventory process in order to minimize the company's losses against the estimates made so far. In order to minimize these problems, the authors model the forecasting information system for procurement of goods using VB.Net and MYSQL and combine the Moving Average method. The method used is the data collection and processing, and continued with the data analysis process, to model the system requirements of the writer using UML. The final result of this study is that the value of accuracy reaches 88% so that the inventory forecasting system using the moving average method can help managers in making decisions to determine the process of inventory in the future